Invasive Haemophilus influenzae Disease in Adults ≥65 Years, United States, 2011. (3rd July 2014) - Blain, Amy; MacNeil, Jessica; Wang, Xin; Bennett, Nancy; Farley, Monica M.; Harrison, Lee H.; Lexau, Catherine; Miller, Lisa; Nichols, Megin; Petit, Susan; Reingold, Arthur; Schaffner, William; et al.
Abstract : In this older age group burden of disease and CFR both increase significantly as age increases. Several underlying conditions increased risk of disease severity and patients with severe disease were more likely to die. Abstract: Background. Since the introduction of the Haemophilus influenzae serotype b vaccine, H influenzae epidemiology has shifted. In the United States, the largest burden of disease is now in adults aged ≥65 years. However, few data exist on risk factors for disease severity and outcome in this age group. Methods. A retrospective case-series review of invasive H influenzae infections in patients aged ≥65 years was conducted for hospitalized cases reported to Active Bacterial Core surveillance in 2011. Results. There were 299 hospitalized cases included in the analysis. The majority of cases were caused by nontypeable H influenzae, and the overall case fatality ratio (CFR) was 19.5%. Three or more underlying conditions were present in 63% of cases; 94% of cases had at least 1. Patients with chronic heart conditions (congestive heart failure, coronary artery disease, and/or atrial fibrillation) (odds ratio [OR], 3.27; 95% confidence interval [CI], 1.65–6.46), patients from private residences (OR, 8.75; 95% CI, 2.13–35.95), and patients who were not resuscitate status (OR, 2.72; 95% CI, 1.31–5.66) were more likely to be admitted to the intensive care unit (ICU). Intensive care unit admission (OR, 3.75; 95% CI, 1.71–8.22) and do not resuscitate status (OR, 12.94; 95% CI, 4.84–34.55) were significantly associated with death. Conclusions. Within this age group, burden of disease and CFR both increased significantly as age increased. Using ICU admission as a proxy for disease severity, our findings suggest several conditions increased risk of disease severity and patients with severe disease were more likely to die. Further research is needed to determine the most effective approach to prevent H influenzae disease and mortality in older adults.